COAMO e COAGEL: expansão e formação do cooperativismo agroindustrial na mesorregião centro ocidental paranaense - Oliveira, Dean Gomes de (2016)
The agroindustrial cooperatives in the brazilian agricultural scenario are substantial, since they are responsible for a significant number of employees, members and products, thus research them is essential in any field, whether economic, political or social. The evolution of brazilian cooperativism occurred at different scales, being pertinent at the agricultural modernization process and mainly by public policies, such as the creation of the Real Plan, which led cooperatives to new guidelines, given the lack of support from the federal government in the 1990s. Therefore, this discusses the agro-industrial cooperative expansion and formation in the central-west region of Paraná State, with emphasis on the two major agro-industrial cooperatives on site, Coamo Agro-industrial Cooperativa and the suppressed Cooperativa Agroindustrial de Goioerê - Coagel. In this sense, the search aimed to analyze the factors that led Coamo to become the largest single cooperative in Latin America, and Coagel to be merged into this, also trying to understand this whole process from the local, with its specificities. The hypothesis of the research is that among the factors that conditioned Coamo performance, was its vertical integration process, along with its territorial expansion, which has already reached three brazilian states (PR / SC / MS). Still, Coagel entered into crisis after the decline of cotton in 1996, which was the flagship of the cooperative, initially causing its lease, then its merger into Coamo. In short, it is considered that this study highlights the different paths and strategic profiles embraced for the hegemony of Coamo, both in the field as in the city, such as the difficulties encountered by Coagel in the course of its history.